Cancer stem cells and radioresistance. (August 2014) - Rycaj, Kiera; Tang, Dean G.
Abstract Purpose: Radiation therapy has made significant contributions to cancer treatment. However, despite continuous improvements, tumor recurrence and therapy resistance still occur in a high proportion of patients. One underlying reason for this radioresistance might be attributable to the presence of cancer stem cells (CSC). The purpose of this review is to discuss CSC-specific mechanisms that confer radiation resistance. Conclusions: We focus our discussions on breast cancer and glioblastoma multiforme (GBM) and conclude that both CSC-intrinsic and CSC-extrinsic factors as well as adaptive responses in CSC caused by irradiation and microenvironmental changes all make contributions to CSC-mediated radioresistance. Our discussions emphasize CSC as novel therapeutic targets in order to potentiate radiotherapy efficacy.